2014
DOI: 10.1177/0971852414529481
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood at your Fingertips: Transforming Community Online through a Canadian Social Networking Site for Mothers

Abstract: Local geographical communities have changed significantly in the last several decades due to a number of cultural factors, including women's increased participation in the paid workforce and growing rates of single parenthood. Changing communities have resulted in increased social isolation for mothers raising young children, which often means a lack of vital social support, particularly from other mothers. The current research addresses this contemporary challenge by exploring the role of a Canadian social ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 36 publications
0
28
0
1
Order By: Relevance
“…The divisions between private and public, individual and collective, are ultimately disrupted through individual women connecting to a community of other women online-a central recognition within cyberfeminism's potential Downloaded by [University of Otago] at 10:55 30 July 2015 for positive transformation (Daniels, 2009). When women feel a sense of community and support, as the mothers in our study overwhelmingly reported (Parry et al, 2013;Valtchanov et al, 2014), women can develop genuine connections and can be more honest, because they do not feel judged (Ley, 2007). The unique dual focus of Momstown, both online and physical connections, facilitated a distinct form of mothers' mediated leisure that promoted an environment of support and nonjudgment.…”
Section: Resisting Motherhood Ideologies Through Mediated Leisurementioning
confidence: 49%
See 3 more Smart Citations
“…The divisions between private and public, individual and collective, are ultimately disrupted through individual women connecting to a community of other women online-a central recognition within cyberfeminism's potential Downloaded by [University of Otago] at 10:55 30 July 2015 for positive transformation (Daniels, 2009). When women feel a sense of community and support, as the mothers in our study overwhelmingly reported (Parry et al, 2013;Valtchanov et al, 2014), women can develop genuine connections and can be more honest, because they do not feel judged (Ley, 2007). The unique dual focus of Momstown, both online and physical connections, facilitated a distinct form of mothers' mediated leisure that promoted an environment of support and nonjudgment.…”
Section: Resisting Motherhood Ideologies Through Mediated Leisurementioning
confidence: 49%
“…Recent research has clearly demonstrated that mothers want to share their experiences and concerns by connecting online with other mothers who can provide social connections, advice, support, and empowerment (Ley, 2007;Madge & O'Connor, 2006;Moravec, 2011;Valtchanov, Parry, Glover, & Mulcahy, 2014). These online connections create a profound sense that mothers are not alone-a message that is "more than a lifeline; it's a revolution" (Samuel, 2011, p. xii).…”
Section: Cybermothersmentioning
confidence: 94%
See 2 more Smart Citations
“…It has long been recognised that individuals can meet on the Internet and form close relationships. However, such relationships are often developed through an extensive period of online communication and in groups where the purpose is the facilitation of interpersonal support (e.g., Valtchanov, Parry, Glover, & Malcahy, ).…”
Section: Discussionmentioning
confidence: 99%